(untitled) (Bangladesh Journal of Medical Science, 2026)
Bone growth stimulants (BGS) are increasingly used to enhance osseointegration in dental implants, but their efficacy remains debated. This meta-analysis evaluates the impact of BGS on bone regeneration and implant success. Following PRISMA guidelines, 25 studies (2000–2024) were analyzed. Random-effects models pooled effect sizes for outcomes like bone density and implant survival. Subgroup analyses compared graft types (autografts, alloplastics, bio-enhanced grafts). BGS improved osseointegration (pooled ES: 1.22, 95% CI: 0.95– 1.50), with bio-enhanced grafts showing the highest efficacy (ES: 1.43). Bioactive coatings (ES: 1.26) outperformed strontium coatings (ES: 0.94), while bisphosphonates negatively impacted outcomes (ES: -1.96). Heterogeneity was low (I² = 9.08%), but publication bias was detected (Egger’s test: *p* = 0.025). BGS, especially combination grafts, enhance implant stability, though patient-specific factors must guide clinical use. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S36-S49